Strategy to Avoid Negative Perception on Game - Yedija Prima Putra; Hendra Prasetya (SISFORMA, 2014)
In the beginning, games are made to provide entertainment. But, with the interesting entertainment, some game developers use that just for their own benefit. Moreover, many of them including elements of violence and pornography on their games. That is just only to make more profit for them. Thats why some parents are anxious and have a bad view of games. But, not all of the games have elements of violence and pornography. Some of developers make game which is including educational value. "Crazy Machines 2" is one of many games which has educational value. This is one of the ways to Avoid Negative Perception on Game. Key Word : game, creativity, strategy, avoid negative perception